THE FEATURES OF STRATEGIC MANAGEMENT OF THE TOURIST ENTERPRISE - Kaziuka , N.P. (The actual problems of regional economy development, 2020)
The article summarizes the approaches to defining the concept of strategic management for tourism industry enterprises. The analysis of the main processes in the cycle of strategic management in the practice of tourism industry enterprises and the stages of strategic planning as a basic platform of strategic management are considered, specific features of strategic management of the tourist enterprise are singled out. The factors of construction and implementation of an effective strategy are highlighted for the development of a tourism enterprise in the context of global integration into the global tourism industry. The definition of strategic management and strategic planning is generalized, their specificity for tourism business enterprises is singled out. The peculiarities of the functioning of the sphere of tourism in the context of forming the strategy of tourist enterprises are given. The generalization of aspects of strategic planning as a basis of strategic management is carried out. The stages of strategic planning are considered, as well as its advantages are highlighted. The article substantiates that strategic management covers a wide range of organizational decisions about situations focused on future development, which are related to the general goals of the travel agency and are under the influence of an uncontrolled external environment. The directions of development of strategic management as elements of maintenance of management of strategic possibilities of firm are defined. It is proved that tourism is an industry that is characterized by a high level of uncertainty due to the impact on its development of political, economic, legal, socio-economic factors; effective development of the tourism industry is impossible without well-thought-out strategic planning, especially at the stage of creating and entering the market of the tourism business. It is proved that the management of a tourist enterprise must determine the vision of development prospects by developing and future implementation of the strategy, mission and goals of the company, and the development of tourism in Ukraine should be in accordance with global tourism trends and trends. The factors that inhibit the development of the market of tourist services in Ukraine, as well as strategic guidelines in tourism management are highlighted.